Earthquake-triggered landslides and mudflows: Was this the wave that engulfed Ancient Helike?. (December 2020) - Koukouvelas, Ioannis K; Piper, David JW; Katsonopoulou, Dora; Kontopoulos, Nikolaos; Verroios, Sotirios; Nikolakopoulos, Konstantinos; Zygouri, Vasiliki
The destruction of Ancient Helike in 373 BC as reported by ancient Greek and Roman writers is inconsistent with modern evidence on the geological context. The classical view of a strong earthquake, similar to the 1817 M = 6.6 earthquake and followed by a giant tsunami wave that permanently inundated the ruined city does not stand up to modern scrutiny. Evidence for co-seismic slip on the Helike Fault at that time and for a corresponding tsunami have already been shown to be lacking, and the archaeological evidence shows that part of the site was reoccupied within 40 years. New observations on outcrops, excavated sites, and boreholes show that at least two mudflow deposits several metres thick of slightly gravelly mud overlie 4th c. BC archaeological remains on the Katourlas fan. Upstream, landslides are common in the 4 km 2 river basin and could have dammed the ephemeral Katourlas River. Relics of this dam are still recognised in the riverbed as a knickpoint. Temporary damming of rivers by earthquake-triggered landslides is a common phenomenon in northern Peloponnese. The destruction of Ancient Helike appears to have been a localised non-linear cascading series of disasters, with a strong earthquake followed by a destructive mudflow generated by breaching of a landslide-dammed lake in the Katourlas basin. Historical records of flooding from the west may record another landslide dam followed by a more watery flood in the Selinous River. We propose that it was mudflows and floods from inland rather than a tsunami from the sea that contributed to the final destruction of Helike.